OVER REAKSI PASAR TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BURSA EFEK JAKARTA - Adawiyah, Rabi’atul; Faozan, Akhmad (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Overreaction phenomenon is one of the most complexity problem to make an efficient stock market. This research investigates are go public manufacturer company has an overreaction indicate, with year 2003 until 2005 scop. The methode that utilize threathen to Rahmawati and Tri (2005), calculation based on Jogiyanto (2000) formula. The finding of the research indicates there is overreaction that shows by loser portofolio to first rate winner portofolio. The comparison average cummulative abnormal return (ACAR) between loser portofolio and winner portofolio showing there’s significant difference. The research is also shown that winner portofolio is more overreacted than loser portofolio. The grouping of winner portofolio in three groups (A, B, C portofolio) and loser portofolio (D, E, F portofolio) according Rahmawati and Tri 2005), produce that Cumulative abnormal return (CAR) from loser portofolio not showing overreaction effect, only in winner portofolio showing overreaction effect.